Histone Deacetylase 6 Inhibitor CKD-WID Suppressed Monosodium Urate-Induced Osteoclast Formation by Blocking Calcineurin-NFAT Pathway in RAW 264.7 Cells - Seong-Kyu Kim; Jung-Yoon Choe; Ji-Won Kim; Ki-Yeun Park (MDPI AG, 2023)
Histone deacetylase (HDAC) has been found to play a crucial role in the regulation of osteoclast differentiation and formation. This study was designed to identify the effect of the HDAC6 inhibitor CKD-WID on the receptor for the activation of nuclear factor-κB ligand (RANKL)-mediated osteoclast formation in the presence of monosodium urate (MSU) in RAW 264.7 murine macrophage cells. The expression of osteoclast-specific target genes, calcineurin, and nuclear factor of activated T-cells cytoplasmic 1 (NFATc1) was evaluated in RAW 264.7 murine macrophages treated with MSU, RANKL, or CKD-WID by real-time quantitative polymerase chain reaction and Western blot assay. The effect of CKD-WID on osteoclast formation was measured by tartrate-resistant acid phosphatase (TRAP) staining, F-actin ring formation staining, and assays for bone resorption activity. RANKL in the presence of MSU significantly induced HDAC6 gene and protein expression in RAW 264.7 cells. CKD-WID markedly suppressed the expression of osteoclast-related markers such as c-Fos, TRAP, cathepsin K, and carbonic anhydrase II induced by co-stimulation with RANKL and MSU in RAW 264.7 cells. Transcription factor NFATc1 mRNA expression and nuclear NFATc1 protein expression induced by co-stimulation with RANKL and MSU were significantly inhibited by CKD-WID treatment. CKD-WID also decreased the number of TRAP-positive multinuclear cells and F-actin ring-positive cells and attenuated bone resorption activity. Co-stimulation with RANKL and MSU increased calcineurin gene and protein expression, which was significantly blocked by CKD-WID treatment. The HDAC6 inhibitor CKD-WID suppressed MSU-induced osteoclast formation through blocking the calcineurin-NFAT pathway in RAW 264.7 cells. This suggests that HDAC6 is considered a therapeutic target in uric acid-mediated osteoclastogenesis.